The interplay of colour and bioacoustic traits in the differentiation of a Southeast Asian songbird complex. Issue 1 (20th November 2020) - Gwee, Chyi Yin; Lee, Qiao Le; Mahood, Simon P.; Hung Le Manh; Tizard, Robert; Eiamampai, Krairat; Round, Philip D.; Rheindt, Frank E.
Abstract: Morphological traits have served generations of biologists as a taxonomic indicator, and have been the main basis for defining and classifying species diversity for centuries. A quantitative integration of behavioural characters, such as vocalizations, in studies on biotic differentiation has arisen more recently, and the relative importance of these different traits in the diversification process remains poorly understood. To provide a framework within which to interpret the evolutionary interplay between morphological and behavioural traits, we generated a draft genome of a cryptic Southeast Asian songbird, the limestone wren‐babbler Napothera crispifrons . We resequenced whole genomes of multiple individuals of all three traditional subspecies and of a distinct leucistic population. We demonstrate strong genomic and mitochondrial divergence among all three taxa, pointing to the existence of three species‐level lineages. Despite its great phenotypic distinctness, the leucistic population was characterized by shallow genomic differentiation from its neighbour, with only a few localized regions emerging as highly diverged. Quantitative bioacoustic analysis across multiple traits revealed deep differences especially between the two taxa characterized by limited plumage differentiation. Our study demonstrates that differentiation in these furtive songbirds has resulted in a complex mosaic of colour‐based and bioacoustic differences among populations. Extreme colour differences can be anchored in few genomic loci and may therefore arise and subside rapidly.